HUBUNGAN ANTARA POLA PERSONAL HYGIENE (VULVA HYGIENE) DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PUTRI DI SMAN II UNGARAN - Wahyuningrum, Tria (JURNAL KEPERAWATAN BINA SEHAT, 2011)
The teenagers do not know much information about health reproduction, they also do not know how to care the genital organs included vagina, so many flour albus cases happen in the teenagers as the effect of the inappropriate caring way of reproduction organ. The purpose of the research is to know the relationship between the pattern of personal hygiene (vulva hygiene) and the flour albus occurrrence on the female teenagers at SMAN II Ungaran.This research was conducted at SMAN II Ungaran on 20thuntil 24thJune 2010 by using descriptive correlation method with case control approach. The sample was taken by using total sampling technique for control group and purposive sampling technique for case group.The result of the research was most of female students of class X at SMAN II Ungaran that suffered pathology flour albus occurrence had bad personal hygiene (vulva hygiene) pattern, the amount was 14 students (33,3%). Most of the female students of class X at SMAN II Ungaran that did not suffer pathology flour albus had good pattern of personal hygiene (vulva hygiene), the amount was 18 students (42,9%). The result of data analysis: x2= 9,882 , p value = 0,002 it means there is correlation between the pattern of personal hygiene and flour albus occurrence.The suggestion for the female teenagers is to increase the health reproduction, especially their vital organ care.Reference : 23 references (1998-2008)Keywords : Personal Hygiene Pattern, Flour Albus Occurrence